2017
DOI: 10.18488/journal.aefr.2017.78.799.808
|View full text |Cite
|
Sign up to set email alerts
|

Is Inequality Harmful for Broadband Diffusion and Economic Growth?

Abstract: Some say that the digital gap adds new inequalities to the economic and social inequalities and help amplify them. However, others think that this gap is simply the effect of the existing social and economic inequalities. Although the first opinion has been studied by a fair number of empirical studies, the second has not had much luck in the existing literature. In this work, we try to examine the impact of inequality on the proliferation of broadband Internet and on the change of its relationship with econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Finally, the logic for the study and methodological support for the data collection and analysis is provided. (Aissaoui, 2017;Tayo et al, 2015;Ugur & Mitra, 2017). Other researchers have also examined the linkages between ICTs and the promotion of individual or community quality of life (Adera et al, 2014;Diga et al, 2013;Kariuki, 2015;Saidi & Douglas, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, the logic for the study and methodological support for the data collection and analysis is provided. (Aissaoui, 2017;Tayo et al, 2015;Ugur & Mitra, 2017). Other researchers have also examined the linkages between ICTs and the promotion of individual or community quality of life (Adera et al, 2014;Diga et al, 2013;Kariuki, 2015;Saidi & Douglas, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, scholars argue that African developing countries still register a gap in the relationship between general ICT diffusion and innovation and socioeconomic growth and development (Asongu, Biekpe, & Tchamyou, 2019;Evans, 2019;Tayo, Thompson, & Thompson, 2015;Ugur & Mitra, 2017). For some, the impact assessment of ICT adoption toward socioeconomic development is based on economic insufficiencies among categories of people and digital divides which are often defined as differences between access and use of ICT infrastructures mostly among impoverished sub-Saharan African populations (Aissaoui, 2017;Penard, Poussing, Mukoko, & Piaptie, 2015). Others reported that the rapid diffusion of technological innovations causes industrial processes (manufacturing and production) to change, which in turn alters the relationship between economic growth and development (Grabowski, 2017).…”
Section: Background Of the Studymentioning
confidence: 99%
See 3 more Smart Citations